2001
DOI: 10.1006/viro.2000.0768
|View full text |Cite
|
Sign up to set email alerts
|

The Epstein–Barr Virus Latent Membrane Protein 1 Induces Interleukin-10 in Burkitt's Lymphoma Cells but Not in Hodgkin's Cells Involving the p38/SAPK2 Pathway

Abstract: Infection of B cells with Epstein-Barr Virus (EBV) induces interleukin-10 (IL-10) production, which may contribute to transformation. IL-10 can modulate the immune response at certain levels, playing a crucial role in balancing humoral and cellular responses. Moreover, it can function as a growth and differentiation factor for B cells. However, the mechanism of IL-10 induction is still unclear. Here we demonstrate that IL-10 was specifically induced by the EBV-latent membrane protein 1 (LMP1) in Burkitt's lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 59 publications
3
73
1
1
Order By: Relevance
“…This inhibition causes a decrease in the constitutively activated STAT3, downregulation of Bcl-2 expression and the tumor cells become sensitive to apoptotic stimuli, including the effect of various chemotherapeutic drugs . Previous reports showed that IL-10 regulation is via p38 MAPK activity (Ma et al, 2001;Vockerodt et al, 2001). We hypothesized, therefore, that p38 MAPK may regulate IL-10 synthesis in the 2F7 cell line.…”
Section: Inhibition Of Il-10 Secretion From 2f7 Cells By Rituximab Ismentioning
confidence: 89%
See 1 more Smart Citation
“…This inhibition causes a decrease in the constitutively activated STAT3, downregulation of Bcl-2 expression and the tumor cells become sensitive to apoptotic stimuli, including the effect of various chemotherapeutic drugs . Previous reports showed that IL-10 regulation is via p38 MAPK activity (Ma et al, 2001;Vockerodt et al, 2001). We hypothesized, therefore, that p38 MAPK may regulate IL-10 synthesis in the 2F7 cell line.…”
Section: Inhibition Of Il-10 Secretion From 2f7 Cells By Rituximab Ismentioning
confidence: 89%
“…It has been reported that IL-10 induction is accompanied by an enhanced phosphorylation of p38/SAPK2 in the Burkitt's lymphoma cell line BL2 (Vockerodt et al, 2001). Other studies have shown that activation of the mitogen-activated protein kinase (MAPK) signaling pathway regulates the activation of Sp1, which in turn regulates the transcription of the hIL-10 gene (Pedersen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, in this case, the contribution of this sequence motif is dependent on the NF-B-like binding site at Ϫ52/Ϫ43, since any promoter fragments that lack the latter are not responsive to LMP1. It has also been shown that the mitogen-activated protein kinase p38 and NF-B contribute to the transactivation of certain LMP-1-inducible genes, such as IL-6, IL-8, and IL-10, through coregulation of their promoter sequences (33,116). In a preliminary experiment, however, a well-established and specific inhibitor of p38 activation (SB203580) (112) did not affect transactivation of the bfl-1 promoter by LMP1 in DG75 cells (result not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For example, IL-6 enhances the growth of LCLs in mouse models of LPD (48,55), and some freshly explanted cells from EBV-positive LPD are dependent on autocrine/paracrine secretion of IL-10 for growth and survival (30). Three different EBV gene products, including the latent LMP1 and EBVencoded RNA gene products and the IE lytic protein, BZLF1, have been reported to induce expression of cellular IL-10 (cIL-10) (28) (24,60). EBV also encodes a lytic viral homolog of IL-10, vIL-10 (16), which likewise enhances the growth of B cells (46).…”
mentioning
confidence: 99%